Letter: complex interplay between obesity and Clostridium difficile infection—authors' reply. Issue 6 (14th August 2017) - Mulki, R.; Katz, P.
Abstract : Linked Content This article is linked to Mulki et al and Kapur and Nagaraja papers. To view these articles visithttps://doi.org/10.1111/apt.13832 andhttps://doi.org/10.1111/apt.14229 .